A Strength Endurance Exercise Paradigm Mitigates Deficits in Hypoglossal-Tongue Axis Function, Strength, and Structure in a Rodent Model of Hypoglossal Motor Neuron Degeneration - Murphy, Erika R.; Thompson, Rebecca; Osman, Kate L.; Haxton, Chandler; Brothers, Margaret; Lee, Li; Warncke, Kristen; Smith, Catherine L.; Keilholz, Amy N.; Hamad, Ali; Golzy, Mojgan; Bunyak, Filiz; et al. (Frontiers in Neuroscience, 2022)
The tongue plays a crucial role in the swallowing process, and impairment can lead to dysphagia, particularly in motor neuron diseases (MNDs) resulting in hypoglossal-tongue axis degeneration (e.g., amyotrophic lateral sclerosis and progressive bulbar palsy). This study utilized our previously established inducible rodent model of dysphagia due to targeted degeneration of the hypoglossal-tongue axis. This model was created by injecting cholera toxin B conjugated to saporin (CTB-SAP) into the genioglossus muscle of the tongue base for retrograde transport to the hypoglossal (XII) nucleus via the hypoglossal nerve, which provides the sole motor control of the tongue. Our goal was to investigate the effect of high-repetition/low-resistance tongue exercise on tongue function, strength, and structure in four groups of male rats: 1) control + sham exercise (n=13); 2) control + exercise (n=10); 3) CTB-SAP + sham exercise (n=13); and 4) CTB-SAP + exercise (n=12). For each group, a custom spout with adjustable lick force requirement for fluid access was placed in the home cage overnight on days 4 and 6 post-tongue injection. For the two sham exercise groups, the lick force requirement was negligible. For the two exercise groups, the lick force requirement was set to ~40% greater than the maximum voluntary lick force for individual rats. Following exercise exposure, we evaluated the effect on hypoglossal-tongue axis function (via videofluoroscopy), strength (via force-lickometer), and structure (via MRI of the brainstem and tongue in a subset of rats). Results showed that sham-exercised CTB-SAP rats had significant deficits in lick rate, swallow timing, and lick force. In exercised CTB-SAP rats, lick rate and lick force were preserved; however, swallow timing deficits persisted. MRI revealed corresponding degenerative changes in the hypoglossal-tongue axis that were mitigated by tongue exercise. These collective findings suggest that high-repetition/low-resistance tongue exercise in our model is a safe and effective treatment to prevent/diminish signs of hypoglossal-tongue axis degeneration. The next step is to leverage our rat model to optimize exercise dosing parameters and investigate corresponding treatment mechanisms of action for future translation to MND clinical trials.